Urgensi nahwu dan shorof sebagai kunci cabang keilmuan dan bahasa Arab dalam agama Islam - Amin, Azkiya Rafida (Maliki Interdisciplinary Journal, 2024)
The command to seek knowledge has been explained in the Qur'an and hadith. As Muslims, we need to learn the knowledge that is mandatory, such as monotheism and tafsir. Various branches of knowledge in Islam were born from the Middle East, so that various books written by friends and Ulama' were written in Arabic, and without harokat. Remembering that at that time Arabs did not yet know about Harokat. This often makes readers make mistakes in reading or interpreting the writing. This event has fatal consequences if someone reads the Qur'an incorrectly due to a mistake in Harokat, which can change the meaning. Therefore, there is a need for learning related to Arabic grammar and linguistic, namely Nahwu and Shorof. To avoid misinterpretation and avoid misunderstandings.